Measurements of four-lepton production at Z resonance in pp collisions at √s=7 and 8 TeV with ATLAS - Aad, Georges; Anders, Christoph; Andrei, George Victor; Brandt, Oleg; Colombo, Tommaso; Davygora, Yuriy; Dietzsch, Thorsten; Dunford, Monica; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; Kasieczka, Gregor; et al. (Physical review letters, 2014)
Measurements of four-lepton (4ℓ, ℓ=e,μ) production cross sections at the Z resonance in pp collisions at the LHC with the ATLAS detector are presented. For dilepton and four-lepton invariant mass regions mℓ+ℓ−>5 GeV and 80<m4ℓ<100 GeV, the measured cross sections are 76±18(stat)±4(syst)±1.4(lumi) fb and 107±9(stat)±4(syst)±3.0(lumi) fb at √s=7 and 8 TeV, respectively. By subtracting the nonresonant 4ℓ production contributions and normalizing with Z→μ+μ− events, the branching fraction for the Z boson decay to 4ℓ is determined to be (3.20±0.25(stat)±0.13(syst))×10−6, consistent with the standard model prediction.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 11.02.2021